The association of androgenetic alopecia and insulin resistance is independent of hyperandrogenemia: A case‐control study. (17th March 2015) - Kartal, Demet; Borlu, Murat; Çınar, Salih L; Ferahbaş, Ayten; Ulaş, Yılmaz; Ünlühızarcı, Kürşad; Ukşal, Ümit; Keleştimur, Fahrettin
Abstract: Background/Objectives: Androgenetic alopecia (AGA) occurs due to the effect of androgens and genetic predisposition. The association between hyperandrogenism and insulin resistance (IR) has been clearly documented. In recent years there have been reports supporting the presence of IR in AGA. The study aimed to investigate the presence of IR in women with AGA and discern whether or not it is associated with hyperandrogenism. Methods: Overall, 77 women with AGA were included in the study. Patients with Ludwig grades I–III AGA were enrolled in the study. Blood samples were drawn for measurements of hormone profile, basal insulin and fasting blood glucose (FBG). An oral glucose tolerance test was performed on another day. IR was assessed by the homeostasis model assessment score. Results: All IR parameters were significantly higher in the 75 study subjects without DM than in the control group ( P  < 0.05). After excluding five patients with IGT, the level of all IR parameters were still higher than in the control group ( P  < 0.05). Hyperandrogenemia was found in 30 (40%) patients. When this second group ( n  = 45) (excluding patients with hyperandrogenemia) was compared with the control group on IR, all parameters except for basal insulin were significantly higher in the second group than in the controls ( P  < 0.05). Conclusion: Our results suggest a relation between IR and AGA in female patients. We showed for the first time that the association of AGA and IR is independent of hyperandrogenemia.